2019
DOI: 10.1002/mc.23006
|View full text |Cite
|
Sign up to set email alerts
|

miR‐20a inhibits hypoxia‐induced autophagy by targeting ATG5/FIP200 in colorectal cancer

Abstract: Autophagy is a highly conserved lysosome‐mediated protective cellular process in which cytosolic components, including damaged organelles and long‐lived proteins, are cleared. Many studies have shown that autophagy was upregulated in hypoxic regions. However, the precise molecular mechanism of hypoxia‐induced autophagy in colorectal cancer (CRC) is still elusive. In this study, we found that miR‐20a was significantly downregulated under hypoxia in colon cancer cells, and overexpression of miR‐20a alleviated hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 66 publications
(110 reference statements)
0
21
0
Order By: Relevance
“…Additionally, Zheng et al [ 35 ] suggested that ATG5 inhibition contributed to treatment for esophageal carcinoma patients. Furthermore, autophagy abolition through the ATG5/7 re-sensitized EC109/CDDP knockdown or the use of pharmacological inhibitors is greatly significant [ 36 ] not only in the esophageal, but also in gastric [ 37 ], colorectal [ 38 , 39 ], bladder [ 40 ], ovarian [ 41 ], and prostate cancers [ 42 ]. With regard to TBK1, it has been proven that TBK1 takes part in modulating cell growth and autophagy [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Zheng et al [ 35 ] suggested that ATG5 inhibition contributed to treatment for esophageal carcinoma patients. Furthermore, autophagy abolition through the ATG5/7 re-sensitized EC109/CDDP knockdown or the use of pharmacological inhibitors is greatly significant [ 36 ] not only in the esophageal, but also in gastric [ 37 ], colorectal [ 38 , 39 ], bladder [ 40 ], ovarian [ 41 ], and prostate cancers [ 42 ]. With regard to TBK1, it has been proven that TBK1 takes part in modulating cell growth and autophagy [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…As we know, autophagy plays a vital role in various physiologic and pathologic processes containing tumorigenesis (15,16). ATG5, as one of the critical regulators of autophagy, can be regulated by various genes contributing to tumorigenesis, tumor progression, and chemo-/radio-resistance (8,(17)(18)(19)(20). However, the relation between ATG5 and CDKL3 in tumors was firstly revealed in our report.…”
Section: Discussionmentioning
confidence: 66%
“…For example, hypoxia-induced autophagy promotes the occurrence and progression of CRC via the PRKC/PKC-EZR pathway ( 36 ). Che et al reported that miR-20a suppressed hypoxia-induced autophagy by targeting ATG5/FIP200 in CRC ( 37 ). Therefore, to gain a better under-standing of the molecular regulatory mechanisms underlying circCCDC66, the present study examined the association between miR-3140 and autophagy.…”
Section: Discussionmentioning
confidence: 99%